Single pot conversion of furfuryl alcohol to levulinic esters and gamma-valerolactone in the presence of sulfonic acid functionalized ILs and metal catalysts - Hengne, Amol M.; Kamble, Sumit B.; Rode, Chandrashekhar V. (Green Chemistry, 2013)
Ionic liquids functionalized with acidic anions, HSO4, ClSO3H, PTSA, TFA (MIm), HSO4 and TFA (NMP) were found to efficiently (99% conversion) catalyze the alcoholysis of furfuryl alcohol (FAL) in the presence of methanol, ethanol, n-butanol and isopropyl alcohol (IPA) to the corresponding levulinic acid esters under mild temperature (90-130 degrees C) conditions. The extended alkyl chain length of [MIm] using 1,4-butane sultone enhanced the Bronsted acidity of [BMIm-SH][HSO4] catalyst resulting into the highest selectivity of >95% to Me-LA. An increase in both temperature and catalyst concentration increased the furfuryl alcohol conversion and selectivity to levulinate esters. In contrast, an increase in the substrate concentration from 5 to 15% caused a decrease in Me-LA selectivity due to accumulation of intermediate ethers of furfuryl alcohol. Using a combination of [BMIm-SH][HSO4] and 5% Ru/C catalyst, direct conversion of FAL to gamma-valerolactone (GVL) is shown for the first time. A complete conversion of FAL with the highest selectivity of 68% to GVL could be achieved under optimum conditions while higher Ru loading enhanced the GVL selectivity to 94% in the hydrogenation step of this tandem approach. Our catalyst system could be efficiently recycled five times retaining the original activity and selectivity levels.